2005
DOI: 10.1016/j.cub.2005.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Separate Docking Sites on ERK2 Regulate Distinct Signaling Events In Vivo

Abstract: Inhibitors of the oncogenic Ras-MAPK pathway have been intensely pursued as therapeutics. Targeting this pathway, however, presents challenges due to the essential role of MAPK in homeostatic functions. The phosphorylation and activation of MAPK substrates is regulated by protein-protein interactions with MAPK docking sites. Active ERK1/2 (extracellular signal-regulated kinase 1/2)-MAPKs localize to effectors containing DEF (docking site for ERK, (F)/(Y) -X-(F)/(Y) -P)- or D-domain (docking domain) motifs. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 25 publications
6
100
0
Order By: Relevance
“…Emerging studies in the last few years have provided compelling evidence that these binding sites for docking motifs play a key role in determining the substrate specificity of MAPKs (Biondi and Nebreda, 2003;Tanoue and Nishida, 2003;Dimitri et al, 2005;Ho et al, 2006). The best described docking motif is known as docking site for ERK and JNK (DEJL) or D motif (Chang et al, 2002;Lee et al, 2004;Callaway et al, 2005;Zhou et al, 2006) which posses the general pattern (Arg/Lys) 1À2 -(X) 2-6 -+ A -X-+ B , where + A and + B are hydrophobic residuesleucine (Leu), isoleucine (Ile) or valine (Val).…”
Section: The Structure Of Mapksmentioning
confidence: 99%
“…Emerging studies in the last few years have provided compelling evidence that these binding sites for docking motifs play a key role in determining the substrate specificity of MAPKs (Biondi and Nebreda, 2003;Tanoue and Nishida, 2003;Dimitri et al, 2005;Ho et al, 2006). The best described docking motif is known as docking site for ERK and JNK (DEJL) or D motif (Chang et al, 2002;Lee et al, 2004;Callaway et al, 2005;Zhou et al, 2006) which posses the general pattern (Arg/Lys) 1À2 -(X) 2-6 -+ A -X-+ B , where + A and + B are hydrophobic residuesleucine (Leu), isoleucine (Ile) or valine (Val).…”
Section: The Structure Of Mapksmentioning
confidence: 99%
“…ERK contains a DEF motif-binding pocket and a common D-domain that bind DEF motifs and D-domains, respectively. Single point mutations on the ERK2 DEF motif-binding pocket or the ERK2 common D-domain can impair the signaling to DEF motif-or D-domain-containing interactors of ERK2, respectively, without greatly affecting its overall kinase activity (19). A recent study revealed that ERK2 (but not ERK1) overexpression is sufficient to induce EMT via its DEF motif signaling in human breast epithelial cells (16).…”
mentioning
confidence: 99%
“…68 In agreement with these results, D-peptides impair signal transduction towards the docking-dependent substrate Rsk while preserving the ability to phosphorylate and activate substrates more dependent on FxF docking interactions, such as c-fos, that is inhibited by DEF (FxF)-peptides. 69 These results demonstrate that transmission of signals towards distinct subsets of partners are ruled by specific docking interactions, such as those of FxF (DEF) vs. ØxØ (D) motifs, and can thus be functionally separated in cells without grossly affecting MAPK catalytic activity.…”
Section: Novel Implications Of Mapk Docking Interactionsmentioning
confidence: 77%